Electron transport across magnetic field in gas-discharge nonneutral electron plasma - Kervalishvili, Nikoloz A. (Journals of Georgian Geophysical Society, 2015)
For investigation of the influence of vortex structures and asymmetry of electric and magnetic fields on the processes of electron transport across the magnetic field, the model of electron sheath considered in [1,2] has been used. The investigations were carried out by comparison and analysis of experimental and theoretical dependencies of discharge current on the magnetic field and on the value of disturbance of field symmetry. The obtained results give evidence that the disturbance of field symmetry causes the neoclassical transport of electrons, and the influence of vortex structure on the discharge electron sheath leads to the transverse mobility of electrons strongly different from that of classical.